Gut microbiota as a biomarker and modulator of anti-tumor immunotherapy outcomes - Yan, Jiexi; Yang, Lu; Ren, Qingmiao; Zhu, Chan; Du, Haiyun; Wang, Zhouyu; Qi, Yaya; Xian, Xiaohong; Chen, Dongsheng (Frontiers in Immunology, 2024)
Although immune-checkpoint inhibitors (ICIs) have significantly improved cancer treatment, their effectiveness is limited by primary or acquired resistance in many patients. The gut microbiota, through its production of metabolites and regulation of immune cell functions, plays a vital role in maintaining immune balance and influencing the response to cancer immunotherapies. This review highlights evidence linking specific gut microbial characteristics to increased therapeutic efficacy in a variety of cancers, such as gastrointestinal cancers, melanoma, lung cancer, urinary system cancers, and reproductive system cancers, suggesting the gut microbiota’s potential as a predictive biomarker for ICI responsiveness. It also explores the possibility of enhancing ICI effectiveness through fecal microbiota transplantation, probiotics, prebiotics, synbiotics, postbiotics, and dietary modifications. Moreover, the review underscores the need for extensive randomized controlled trials to confirm the gut microbiota’s predictive value and to establish guidelines for microbiota-targeted interventions in immunotherapy. In summary, the article suggests that a balanced gut microbiota is key to maximizing immunotherapy benefits and calls for further research to optimize microbiota modulation strategies for cancer treatment. It advocates for a deeper comprehension of the complex interactions between gut microbiota, host immunity, and cancer therapy, aiming for more personalized and effective treatment options.